ANALISIS KEPUTUSAN PEMBELIAN ULANG PELANGGAN YANG MENGGUNAKAN APLIKASI SHOPEE PADA MAHASISWA - Mayla Surveyandini; Nurul Hartiti; Arinastuti Arinastuti (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine and analyze the effect of website quality variables (X1), ease of use (X2), security (X3), and customer experience (X4) on repurchase decisions (Y) on the Shopee e-commerce application. The sampling technique used purprosive sampling, with a sample of 100 respondents. The analysis technique used is multiple regression analysis technique with SPSS program. For the feasibility test of the model, the F test is used, with the value of Fcount (56.516) > Ftable (2.696), then the model is declared feasible. Meanwhile, the results of the t-test analysis show that website quality, ease of use, security and customer experience have a positive and significant impact on repurchase decisions, namely by tcounting the variables of website quality (3.667), ease of use (4.144), security (2.637), and customer experience (2,637) is greater than ttable (5,246). Thus, the first, second, third and fourth hypotheses in this study are accepted.